2012
DOI: 10.1007/s11033-012-2465-3
|View full text |Cite
|
Sign up to set email alerts
|

Different patterns of DNA methylation of the two distinct O6-methylguanine-DNA methyltransferase (O6-MGMT) promoter regions in colorectal cancer

Abstract: Colorectal cancer (CRC) is the third most common cancer worldwide. Colorectal cancer incidence differs widely among different geographic regions. In addition to mutational changes, epigenetic mechanisms also play important roles in the pathogenesis of CRCs. O6-methylguanine-DNA methyltransferase (O(6)-MGMT) is a DNA repair protein and in the absence of MGMT activity, G-to-A transition may accumulate in the specific genes such as K-ras and p53. To identify which CpG sites are critical for its downregulation, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 34 publications
0
18
1
Order By: Relevance
“…Therefore, DNA integrity and DNA repair enzymes are crucial especially in IBD patients. MGMT removes alkyl adducts from the DNA especially O6-methylguanine, which is read as an adenine by the DNA polymerase (Mokarram, et al, 2013). Our promising results in recent publication showed that MGMT-B methylation is significantly associated with Kras gene mutation rather than MGMT-A (Mokarram, et al, 2013).…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Therefore, DNA integrity and DNA repair enzymes are crucial especially in IBD patients. MGMT removes alkyl adducts from the DNA especially O6-methylguanine, which is read as an adenine by the DNA polymerase (Mokarram, et al, 2013). Our promising results in recent publication showed that MGMT-B methylation is significantly associated with Kras gene mutation rather than MGMT-A (Mokarram, et al, 2013).…”
Section: Discussionmentioning
confidence: 63%
“…MGMT removes alkyl adducts from the DNA especially O6-methylguanine, which is read as an adenine by the DNA polymerase (Mokarram, et al, 2013). Our promising results in recent publication showed that MGMT-B methylation is significantly associated with Kras gene mutation rather than MGMT-A (Mokarram, et al, 2013). Defect in MGMT leads to G to A transition mutation which shown in CRC patients with K-ras mutation (Mokarram, et al, 2013).…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations